UJI KUALITAS AIR PADA SUMBER MATA AIR SUNGAI AYUNG MENGGUNAKAN METODE INDEKS PENCEMARAN - Nada, I Made; Mahendra Dewi, Ni Luh Putu; Satya Graha, I Made; Windu Dwipayana, Made (Jurnal Ecocentrism, 2024)
The Ayung River spring water source is used by the community for religious activities such as melukat and for bathing water, of course it is necessary to pay attention to the quality of the spring water source. The water quality at the Ayung River spring water source can be determined by testing the water quality using physical, chemical and biological parameters. The test results are adjusted to the water quality standards table based on Bali Governor Regulation Number 16 of 2016 to determine the quality of water that has been tested. Then the test result were analyzed using the Pollution Index (IP) method to determine the level of water pollution at the Ayung River spring water source. Based on the result of the analysis, it was found that at point 1 Beji Karang Dalem got an IP score of 1.36 with a lightlu polluted status and at point 2 Pesiraman Dukuh Sakti got an IP score of 1.75 with a lightly polluted status.